PENGEMBANGAN MODEL ASESMEN KEMAMPUAN MENGAJAR MAHASISWA-GURU DI FKIP UNIVERSITAS TERBUKA - Siti Julaeha; Amalia Sapriati (LPPM Universitas Terbuka, 2016)
This article was written based on research to produce a model and assessment system of teachers' teaching ability, which can be utilized by teacher education institutions, especially teacher distance education institusion. This research needs to consider the need for: (1) the development of teaching ability that can improve students' high thinking ability, (2) assessment model which is relevant to learning achievement, (3) the implementation of various and feasible assessments for students, and (4) application of learning achievement model and system by taking into account the spread of domicile of students who attend the distance education program. The data were collected through expert evaluation of teaching ability and teaching skills assessment models and focus group discussions with the academic staff involved in the implementation of assessment in distance education. The nature of the research is descriptive qualitative, supplemented with quantitative data. An assessment model for primary teaching ability resulted by the research, for effective implementation, stipulates the provision of: (1) class for practice and performance test and laboratory for practicum; (2) mentors/instructors, examiners, and IT staff with adequate quantity and quality; as well as (3) guidelines and procedures as reference of all parties involved in the implementation of the assessment. Artikel ini ditulis berdasarkan penelitian untuk menghasilkan model dan sistem asesmen kemampuan mengajar guru, yang dapat dimanfaatkan oleh lembaga pendidikan guru, khususnya lembaga pendidikan guru jarak jauh. Penelitian ini dilakukan dengan mempertimbangkan perlunya: (1) pengembangan kemampuan mengajar yang dapat meningkatkan kemampuan berpikir tingkat tinggi siswa, (2) model asesmen penilaian yang relevan dengan capaian pembelajaran, (3) pelaksanaan asesmen yang bervariasi dan feasible bagi mahasiswa, serta (4) penerapan model dan sistem asesmen capaian pembelajaran dengan mempertimbangkan ketersebaran domisili mahasiswa yang mengikuti pendidikan jarak jauh. Data dikumpulkan melalui evaluasi pakar terhadap rumusan kemampuan mengajar dan model asesmen kemampuan mengajar serta melalui focus group discussion dengan staf yang berkepentingan dengan pelaksanaan asesmen dalam pendidikan jarak jauh. Analisis data/informasi dilakukan secara deskriptif kualitatif dan kuantitatif sesuai dengan jenis data yang dikumpulkan. Hasil penelitian menyatakan bahwa model hipotetik untuk asesmen kemampuan mengajar mahasiswa-guru Program S1 PGSD menuntut penyediaan: (1) kelas untuk praktik dan ujian praktik serta laboratorium untuk praktikum; (2) pembimbing/instruktur, penguji, dan staf IT dengan jumlah dan kualitas yang memadai; serta (3) pedoman/panduan dan prosedur sebagai acuan semua pihak yang terlibat dalam pelaksanaan penilaian.